2015
DOI: 10.1002/ijc.29831
|View full text |Cite
|
Sign up to set email alerts
|

A potent immunotoxin targeting fibroblast activation protein for treatment of breast cancer in mice

Abstract: Fibroblast activation protein (FAP) is highly expressed in the tumor-associated fibroblasts (TAFs) of most human epithelial cancers. FAP plays a critical role in tumorigenesis and cancer progression, which makes it a promising target for novel anticancer therapy. However, mere abrogation of FAP enzymatic activity by small molecules is not very effective in inhibiting tumor growth. In this study, we have evaluated a novel immune-based approach to specifically deplete FAP-expressing TAFs in a mouse 4T1 metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 53 publications
0
65
0
Order By: Relevance
“…In this context, it is conceivable that surface markers expressed mainly, if not exclusively, by MSC should be considered to regulate the TME. Indeed, FAP, CD73, and CD105 can be considered as suitable markers to target MSC [11,13,14,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150]. In hematological malignancies, but also in solid tumors, the administration of immunomodulatory drugs (IMiDs) derived from their prototype Thalidomide to CC-122 has given very attractive results because these compounds can hit MSC besides tumor cells [151,152,153].…”
Section: Drugs That Can Influence Msc-mediated Immune Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is conceivable that surface markers expressed mainly, if not exclusively, by MSC should be considered to regulate the TME. Indeed, FAP, CD73, and CD105 can be considered as suitable markers to target MSC [11,13,14,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150]. In hematological malignancies, but also in solid tumors, the administration of immunomodulatory drugs (IMiDs) derived from their prototype Thalidomide to CC-122 has given very attractive results because these compounds can hit MSC besides tumor cells [151,152,153].…”
Section: Drugs That Can Influence Msc-mediated Immune Regulationmentioning
confidence: 99%
“…Several kinds, compositions, and modes of administration of anti-tumor vaccines have been used with different results [160,161,162,163,164,165,166,167]. More recently, the focus of anti-tumor vaccines has been moved from tumor cells to TME too [7,9,10,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,155,156,157,158,159,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175]. Indeed, the possibility of targeting tumor endothelial cells or the VEGF signaling axis with specific vaccines has been assessed in preclinical studies, and clinical trials are ongoing [168].…”
Section: Msc As Target Cells For Anti-tumor Vaccinesmentioning
confidence: 99%
“… 26 , 30 We have recently found that αFAP-PE38 treatment altered levels of various growth factors, cytokines, chemokines, and matrix metalloproteinases in the tumor microenvironment. 27 Based on the existing CD45 − FAP + stromal population in the B16 melanoma model, as shown in Figure 3b , we hypothesized that αFAP-PE38 treatment might have an additive, or synergistic, effect on the antitumor activity of LV-3Ag immunization. Therefore, the efficacy of LV-3Ag immunization combined with αFAP-PE38 (hereinafter termed “combination treatment”) treatment was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently reported that VEGF produced in the tumor microenvironment enhanced the expression of PD-1 and other inhibitory checkpoints involved in CD8 + T-cell exhaustion. 48 We have previously shown that immunotoxin αFAP-PE38 reduced the level of VEGF in the tumor microenvironment, 27 suggesting that the observed reduction of PD-1 in CD8 + T cells could be partially due to the variation of VEGF. Thus, our current study not only provided proof-of-principle for the use of multiple tumor antigens toward the improvement of antitumor efficacy, but also highlighted the potential of targeting TAFs to improve current immunotherapeutic approaches against cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation